Analisis Kualitas Pelayanan Jasa Labuh Di Unit Pelaksana Teknis Daerah Penyelenggara Angkutan Sungai, Danau, Penyeberangan Dan Laut Provinsi Sumatera Selatan - Malau, Endang R.; Sandy, Amiruddin; Sulastri, Sri (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
Carrying out anchoring activities, the province has the right to determine a distance of 12 miles from sea level, while the remaining rights are under the Ministry of Maritime Affairs and Fisheries. Ship docking service fees are determined in accordance with Government Regulation No. 75 of 2015 concerning Tariffs for Types of Non-Tax State Revenue (PNBP) in the Ministry of Maritime Affairs and Fisheries. This tariff is based on the price set by the port authority in accordance with government regulations, and the calculation is as follows: For ships weighing less than 30 GT that are in port for less than 30 days, rates are calculated based on the number of days used. For ships weighing more than 30 GT which are anchored for less than 30 days, the rate is calculated based on the number of days, length of the ship, and price per ¼ etmal of IDR 750 (IDR 3000). This research aims to analyze the quality of anchoring services in the Regional Technical Implementation Unit for River, Lake, Ferry and Sea Transport (UPTD PASDSPL) South Sumatra Province. The problems identified in this research are delays in issuing bills for docking services and frequent delays in ship departure schedules. The data analysis method used in this research is qualitative data analysis. The results of this research show that overall, UPTD PASDSPL South Sumatra Province provides good anchoring services. However, there are still several obstacles and obstacles, especially related to the long process of issuing docking service bills and frequent delays in ship departure schedules.